Property, plant and equipment disclosure requirements and firm characteristics: the Portuguese accounting standardization system - Botelho, R.; Azevedo, G.; Costa, A.; Oliveira, J. (International Journal of Academic Research in Accounting, Finance and Management Sciences, 2015)
In the new Portuguese accounting frame of reference (Portuguese Accounting Standardization System – Sistema de Normalização Contabilística), the issues related to Property, Plant and Equipment assets are dealt with in the Accounting and Financial Reporting Standard (Norma Contabilística de Relato Financeiro – NCRF) 7 (Property, Plant & Equipment). The present study intends to assess the degree of compliance with the disclosure requirements of this accounting standard by Portuguese unlisted companies. Moreover, it tries to identify the factors that influence their level of disclosure. The financial statements for 2010 and 2011 were content analyzed and a multiple linear regression model was used to assess the motivations for companies to comply with disclosure requirements. Results indicate that older companies with lower levels of foreign activity present higher levels of disclosures. The type of auditing firm is also a factor that influences the level of compliance with NCRF 7.